Eudora Welty, Whiteness, and Race - Pollack, Harriet (Book collections on Project MUSE., 2013)
"Faced with Eudora Welty's preference for the oblique in literary performances, some have assumed that Welty was not concerned with issues of race, or even that she was perhaps ambivalent toward racism. This collection counters those assumptions as it examines Welty's handling of race, the color line, and Jim Crow segregation and sheds new light on her views about the patterns, insensitivities, blindness, and atrocities of whiteness. Contributors to this volume show that Welty addressed whiteness and race in her earliest stories, her photography, and her first novel, Delta Wedding. In subsequent work, including The Golden Apples, The Optimist's Daughter, and her memoir, One Writer's Beginnings, she made the color line and white privilege visible, revealing the gaping distances between lives lived in shared space but separated by social hierarchy and segregation. Even when black characters hover in the margins of her fiction, they point readers toward complex lives, and the black body is itself full of meaning in her work. Several essays suggest that Welty represented race, like gender and power, as a performance scripted by whiteness. Her black characters in particular recognize whiteface and blackface as performances, especially comical when white characters are unaware of their role play. Eudora Welty, Whiteness, and Race also makes clear that Welty recognized white material advantage and black economic deprivation as part of a cycle of race and poverty in America and that she connected this history to lives on either side of the color line, to relationships across it, and to an uneasy hierarchy of white classes within the presumed monolith of whiteness."--Publisher's website